Peningkatan Keterampilan dan Kesejahteraan Masyarakat Pulau Kabung melalui Pelatihan Pembuatan Sirup Pala - Warsidah warsidah; Sukal Minsas; Muliadi Muliadi; Anthoni B Aritonang; Apriansyah Apriansyah; Arie A. Kushadiwijayanto; Mega SJ Sofiana; Yusuf Nurrahman; Risko Risko; Sy. Irwan Nurdiansyah; Ikha Safitri; Shifa Helena (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
The coastal area of Kabung Island is an area of Karimunting Village, Bengkayang Regency, which has a population of around 300 families, whose main livelihood is fishing. Water conditions are very risky due to bad weather, such as strong waves, making it impossible to go to sea, causing new activities for people to plant gardens by utilizing makeshift land and plantation commodities along the hills on the island. Apart from coconuts and cloves, nutmeg is a plantation commodity that is widely available in this region. The training for the processing of syrup from the flesh of the nutmeg for the people of Kabung Island is to improve the skills and welfare of the people of Kabung Island who have previously carried out simple processing of nutmeg by drying the seeds and making candied nutmeg. The training is carried out by direct processing of nutmeg in front of the Kabung island community who are also participants in this activity. This activity was attended by 50 participants consisting of 15 men and 35 women. Based on the questionnaire before the activity started, it showed that 40% had already known and read about the processing of nutmeg syrup, while 30% of the participants had made simple syrup preparations from nutmeg pulp. Then the evaluation conducted after the activity showed that 80% of the participants were able to make good nutmeg syrup, including packaging and labeling of the resulting products.